A crustal‐scale view at rift localization along the fossil Adriatic margin of the Alpine Tethys preserved in NW Italy. Issue 9 (28th September 2015) - Beltrando, Marco; Stockli, Daniel F.; Decarlis, Alessandro; Manatschal, Gianreto
Abstract Fossil rifted margins, whereby originally extended continental crust is subsequently stacked in orogenic belts, provide the opportunity to track rift‐related tectonics across different crustal levels. In this study, the tectonothermal evolution of the fossil Adriatic continental margin, sampled in the Italian Southern Alps, is investigated combining new (U‐Th)/He zircon (ZHe) thermochronology from upper crustal rocks with existing data from the originally underlying lower crust, to shed light on the processes responsible for rift localization in the Alpine Tethys system. The Adriatic microplate records a protracted rift evolution, whereby distributed upper crustal stretching at 245–190 Ma was followed by rift localization along its future western edge, culminating in mantle exhumation at 165–160 Ma. A progressive westward younging of ZHe ages, from 280–240 Ma in the Lombardian Basin to 215–200 Ma near the Sostegno and Fenera Basins, indicates that anomalously high thermal gradients were established in the Late Triassic in the area where rifting later localized. The inferred episodic heating was contemporaneous with protracted fluid flow, minor magmatism, and ductile shearing within the originally underlying lower crust. Subsequent normal faulting was initiated post‐185 Ma, as constrained by exhumation‐related ZHe ages in detrital zircons from a syntectonic sandstone. The spatial distribution of the detected heating‐cooling cycle suggests that rift localization along the western edge of the Adriatic Plate was probably favored by a crustal‐scale thermal anomaly, established at 215–210 Ma, followed by thermal decay by 200–190 Ma. Subsequent crust‐wide extension, starting at 185–180 Ma, led to excision of continental crust and mantle exhumation.